Chemical additives as cold flow improvers for palm oil and jatropha oil biodiesel - Odeigah, Edith Anwunli (2012)
Palm oil and jatropha oil biodiesel are attractive renewable energy source, which could be used as a suitable substitutes for the non-renewable petroleum diesel. Biodiesel produced from these two sources are more environmentally friendly than petroleum diesel and could reduce a nation’s dependence on crude oil imports. However, both biodiesel fuels exhibit very poor cold flow behavior causing engine start-up and fuel filter plugging problems in cold weather. Jatropha oil comparing to palm oil is a very promising source of biodiesel as it is non-edible and can grow in wasteland with very little nutrient requirement and has very high oil yield. Both are the two most widely used oil seeds for biodiesel production in Asia. This study was conducted to evaluate the possibility of using hexane, ethanol, chloroform and kerosene as a cold flow improving component for jatropha and palm biodiesel. 1v/v%, 5v/v%, 10v/v%, 15v/v% and 20v/v% concentrations of these additives in palm and jatropha biodiesels were tested for their effects on the cold flow behavior of the biodiesel fuels as well as on other basic fuel properties such as viscosity, density,flash point and energy content. Performance tests of a Yanmar L48N model single cylinder 4-stroke compression-ignition engine running on palm and jatropha biodiesel containing these additives were then conducted. Among the selected additives, chloroform was found to be the most effective in improving the cold flow behavior of the biodiesel fuels. At 10 v/v% additive concentration, the reduction in cloud point for palm and jatropha biodiesels were respectively 5oC and 6oC with chloroform, 4oC and 5oC with hexane, 4oC and 4oC with ethanol and 3oC and 2oC with kerosene. Kerosene and hexane resulted in good engine performance with about 6.36% and 5.01% increase in brake power at 10v/v%, while ethanol produced a 5.01% increase and chloroform produced a 3.87% decrease in engine brake power at the same concentration. However, overall, ethanol blends seemed to be the most favorable with a good balance between fuel analytical properties and engine performance. Cloud point and pour point were reasonably reduced with ethanol as additive and engine performance was also good because of its higher oxygen content.